A educação sexual formal/informal dos autores de violência sexual contra crianças e adolescentes: contribuições da teoria psicanalítica - Silva, Sabrina do Amarilho Gaspar (2019)
Considering the scarce number of publications that comprise the life history of the Authors of Sexual Violence - AVS against children and adolescents, this study aimed to verify the knowledge that contributed to the formal / informal sexual education process of authors of sexual violence (AVS). For that, we elected as subjects of the research the prisoners of the State Penitentiary of Francisco Beltrao - PFB, in the state of Parana, sentenced for having been authors of sexual violence against children and adolescents. The present research is qualitative and quantitative, empirical and bibliographic. The bibliographic review helped in choosing the following descriptors: Authors of Sexual Violence, Sexual Education of Authors of Sexual Violence, Sexual Education of Abusers, Sexual Education, Authors of Sexual Violence against Children and Adolescents. The consultations were carried out in academic productions from the stricto sensu postgraduate courses, in the Education and Psychology courses at Parana State Universities. However, we did not find productions that covered the same object of our research. The bibliographic review and the research found supported the construction of the questions used in the semi-structured interview, applied to the AVS against children and adolescents. Through this instrument, we investigated the sexual education they received during their childhood and adolescence, considering three social institutions that could have been part of this process. They are: the family, the church and the school. We also investigated the influence of the media in the sexual education process of these subjects. In this way, we seek to understand this sexual education and, from that, observe the limits and possibilities for the transformation of sexual violence against children and adolescents. Our research uses aspects of dialectical historical materialism, insofar as it analyzes the subject in his context, considering the social, political and economic aspects.